2020
DOI: 10.3390/bs10100146
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity, Family Functionality and Mental Health: A Comparative Study between Male and Female Hospitality Workers

Abstract: The aim of the present article is to compare the family functionality, mental health and job insecurity of employees of the hospitality industry in Puerto Vallarta and Bahía de Banderas, in México. This is a quantitative and cross-sectional study. The sample was selected by non-probabilistic sampling for convenience and comprised a total of 914 people, of whom 438 were women (47.92%) and 476 were men (52.08%). The women surveyed reported more somatic symptoms, anxiety, insomnia and social dysfunction compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…It increases feelings of stability, motivation, security, efficiency, productivity, and support. These data are consistent with the investigations by Vargas-Jiménez et al [ 29 ], Menéndez-Espina et al [ 15 ], Lee et al [ 25 ], and Shoss [ 10 ]. Likewise, the fact that job insecurity correlates negatively with family functionality [ 34 , 35 ] is relevant.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It increases feelings of stability, motivation, security, efficiency, productivity, and support. These data are consistent with the investigations by Vargas-Jiménez et al [ 29 ], Menéndez-Espina et al [ 15 ], Lee et al [ 25 ], and Shoss [ 10 ]. Likewise, the fact that job insecurity correlates negatively with family functionality [ 34 , 35 ] is relevant.…”
Section: Discussionsupporting
confidence: 93%
“…This is related to a greater state of insecurity, instability, demotivation and dissatisfaction at work [ 10 , 25 , 33 , 34 , 35 ]. These phenomena are associated with mental health problems such as psychological discomfort caused by a combination of anxiety and depression [ 11 , 28 , 29 , 30 , 31 , 33 ], as well as physical health alterations [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that married female nurses experience intense work–family conflict, have shorter sleep durations than single nurses, and are more likely to develop depressive emotions [ 24 ], and working women report more mental health problems than men [ 25 ]. Meanwhile, in China, women are given more responsibility for family care due to the cultural emphasis on family and traditional gender roles [ 26 ].…”
Section: Introductionmentioning
confidence: 99%